2018
DOI: 10.1038/s41598-017-18578-2
|View full text |Cite
|
Sign up to set email alerts
|

Fis is a global regulator critical for modulation of virulence factor production and pathogenicity of Dickeya zeae

Abstract: Dickeya zeae is the causal agent of rice foot rot disease, which has recently become a great threat to rice planting countries and regions. The pathogen produces a family of phytotoxins named zeamines that is critical for bacterial virulence, but little is known about the signaling pathways and regulatory mechanisms that govern zeamine production. In this study, we showed that a conserved transcriptional regulator Fis is involved in the regulation of zeamine production in D. zeae strain EC1. Deletion mutants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 51 publications
3
64
0
Order By: Relevance
“…In fact, this study has verified that the VfmE but not the VfmH regulated the transcription of slyA (Fig. B), and our previous transcriptome analysis of ΔslyA has showed that the expression of vfm genes especially vfmA , vfmD , vfmE , vfmF , vfmU , vfmR and vfmQ was significantly reduced in this mutant, and qRT‐PCR data showed that the expression of vfmE in ΔslyA is only 0.186 ± 0.013‐folds of strain EC1 (Zhou et al , ), additionally, Fis protein directly binds to the promoter of vfmE (Lv et al , ), and SlyA significantly regulates the expression of fis in EC1 (Zhou et al , ), we proposed that zeamine production is regulated in such pathway: SlyA to Fis to zeamines or SlyA to Fis to VfmE to zeamines (Fig. ).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…In fact, this study has verified that the VfmE but not the VfmH regulated the transcription of slyA (Fig. B), and our previous transcriptome analysis of ΔslyA has showed that the expression of vfm genes especially vfmA , vfmD , vfmE , vfmF , vfmU , vfmR and vfmQ was significantly reduced in this mutant, and qRT‐PCR data showed that the expression of vfmE in ΔslyA is only 0.186 ± 0.013‐folds of strain EC1 (Zhou et al , ), additionally, Fis protein directly binds to the promoter of vfmE (Lv et al , ), and SlyA significantly regulates the expression of fis in EC1 (Zhou et al , ), we proposed that zeamine production is regulated in such pathway: SlyA to Fis to zeamines or SlyA to Fis to VfmE to zeamines (Fig. ).…”
Section: Discussionsupporting
confidence: 72%
“…The unlabelled vfmE DNA promoter fragments of 100 and 200‐fold as the competitor, were used in competition with the labelled DNA promoter fragments in the binding assay with the VfmH‐GST fusion protein and its derivatives. The positions of free DNA (F) and of protein‐DNA complexes (C) were shown and the GST∙tag protein is unable to bind to the promoter DNAs (Lv et al, ). B.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the deletion of Flp in Xcc caused a series of changes in virulence and HRassociated phenotypes. Although virulence factor regulation by Fis has been seen in other bacterial plant pathogens such as Dickeya dadantii (Ouafa et al, 2012) and Dickeya zeae (Lv et al, 2018), no role has been attributed to its regulation of HR, suggesting a differentiate role in Xcc.…”
Section: Discussionmentioning
confidence: 99%